Pemurnian Biogas Menggunakan Proses Adsorpsi Dengan Karbon Aktif Sebagai Adsorben - Berlian Mustika Sari; Riyas Hadi Prasojo; Nana Dyah Siswati (Jurnal Serambi Engineering, 2025)
Biogas is a renewable energy source produced by the anaerobic digestion of organic matter.  However, impurities such as carbon dioxide (CO₂) found in raw biogas can reduce its quality as a fuel.  Therefore, a purification process is needed to increase the amount of methane (CH₄) in the biogas.  Adsorption using activated carbon as an adsorbent is one of the efficient purification techniques.  Due to its porous structure and large surface area, activated carbon is very good at absorbing gas pollutants.  By using the adsorption method to reduce the concentration of CO₂, this study aims to increase the amount of methane (CH₄) in biogas.  Changes in the height of the activated carbon adsorption column and the gas flow rate are part of the technique.  With an ideal adsorption efficiency of 96.65% at an adsorbent height of 20 cm and a flow rate of 200 ml/min, the results show that activated carbon is efficient in adsorbing CO₂.  After the adsorption process, the CH₄ content increased to 98.51%, which meets the requirements of the Indonesian National Standard (SNI) for biogas quality.  This research advances the technology for the purification of biogas, which can be used as a renewable energy source.